2016
DOI: 10.1158/0008-5472.can-15-2743
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analysis of Heterogeneous Drug Responses in Acute Myeloid Leukemia That Enables the Discovery of Predictive Biomarkers

Abstract: Many promising new cancer drugs proceed through preclinical testing and early-phase trials only to fail in late-stage clinical testing. Thus, improved models that better predict survival outcomes and enable the development of biomarkers are needed to identify patients most likely to respond to and benefit from therapy. Here, we describe a comprehensive approach in which we incorporated biobanking, xenografting, and multiplexed phospho-flow (PF) cytometric profiling to study drug response and identify predictiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Improved eradication of dRIs during early treatment phases before the subclones evolve would prevent progression to more aggressive, therapy-resistant disease. Prior studies from us and others have shown that xenografting of a wide spectrum of primary patient samples provides a powerful tool to evaluate novel therapeutics and develop biomarkers (23,25,46,47). Our study suggests that extending the xenograft-based drug development paradigm by including genetic analysis to uncover subclonal responses to drug treatment will open up avenues to evaluate whether relapse-fated clones are effectively targeted.…”
Section: Discussionmentioning
confidence: 76%
“…Improved eradication of dRIs during early treatment phases before the subclones evolve would prevent progression to more aggressive, therapy-resistant disease. Prior studies from us and others have shown that xenografting of a wide spectrum of primary patient samples provides a powerful tool to evaluate novel therapeutics and develop biomarkers (23,25,46,47). Our study suggests that extending the xenograft-based drug development paradigm by including genetic analysis to uncover subclonal responses to drug treatment will open up avenues to evaluate whether relapse-fated clones are effectively targeted.…”
Section: Discussionmentioning
confidence: 76%
“…However, in the search for agents that produce durable responses, the question is not whether an agent can achieve these immediate goals, but whether it can eliminate the cells responsible for disease initiation, maintenance, and progression. Based on accumulating evidence that stem and progenitor cells play pivotal roles in various stages of MDS and AML pathogenesis [, , , , ], it has been suggested that targeting one or more of these populations will likely be necessary to eradicate these disorders [, , , , , , , ]. This realization provides the rationale for developing a method to assess the effects of therapeutic agents on MDS and AML stem and progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In 24 samples, CC-90009 significantly reduced CD45 + 33 + AML cells by 52-100% in injected femur (RF) and 62-99% in non-injected bones (BM), compared to vehicle-treated mice ( Figure 6D; Table 1). These samples were termed "responders" in keeping with the classification scheme we previously developed 45 . Eight "partial responders" had a less robust response to CC-90009, with 20% to 60% relative reduction.…”
Section: Cc-90009 Reduces Leukemic Engraftment In Aml Xenograft Modelsmentioning
confidence: 99%